THE CHARACTERSITICS OF DANCE SKILLS IN EARLY ADOLESCENCE - Banevičiūtė, Birutë (Acta Paedagogica Vilnensia, 2007)
The most important goal of dance education in a comprehensive school is to engage students in processes of cognition of inside and outside world and communication of inner experience by means of dance and to develop skills in these processes. Although the problems of dance skills education have been investigated by many scientists the understanding of dance skills concept is unclear and vague. The review of the literature reveals that dance skills are approached mainly from the physical point of view or are focused on separate definitions of skills of choreographers, dancer’s skills or different dance technique skills. This may limit understanding about value and outcome of educating dance skills in a comprehensive school. According to many famous arts education researchers (Davis, Gardner, Vygotsky) period of early adolescence is very complicated not only in psychological and physical domain, but also in arts education: students at this age don’t like to take part in arts activities, especialy in drawing, because they loose their childish spontaneous creativity, motivation, they become more self-critical. It is very important in this period to engage students in interesting, various arts processes, to use appropriate education methods and evaluation appliances. The problems of early adolescence dance education are poorly investigated from these points of view. That’s why the paper focuses on revealing main characteristics of dance skills in early adolescence. According to cognitive arts theory dance skills are approached as skills to express dance elements (movement, space, time, force, dynamics) and relate them into solid structure interpretating and communicating inner experience. In this article the empirical features of dance skills in early adolescence are pointed out and levels of dance skills are defined. To achieve this aim the educational research was held with 159 students of 10–12 years old of two comprehensive schools in Vilnius. The main point of this research was to apply diagnostic prosedures to reaveal dance skills empyrical features and levels. Four creative dance tasks were suggested for teenagers to execute: one to dance alone, one to dance in group of four, one narrative intention, one abstract intention. All tasks demanded improvised dance without music to create best conditions to reveal skills to express rhythm and tempo. Analysing the execution of these tasks appearance of dance elements, duration of dance elements appearance and connection between dance elements was examined. According to the results of analysis levels of dance skills were defined: low, medium and high level. The results of educational research showed that in early adolescence mostly dance skills are revealed at a low level. Only skills to express movement, space and tempo are revealed at a medium level. There is no evidence to maintain that age or gender can influence dance skills higher level. Dance experience of students and their participation in various dance activities (performing, creating and appreciating) influence higher level of dance skills in early adolescence.